The factors impinging on Lebanon’s Dissociation Policy - Daoud, Gilbert (2024)
Despite the Lebanese government’s announcement of a dissociation policy from conflicts in neighboring countries in 2012, a number of internal and external factors hampered Lebanon’s application of this policy. This thesis explores the internal and external factors that include risks and variables in the geopolitical orbit of the Middle East since 2003 that render a dissociation from regional politics unachievable. This will include a comparison with two successful consociational system, Switzerland and Netherland, that succeeded to achieve neutrality and dissociation. Internally, a hallmark of Lebanon's political environment is a deeply entrenched sectarian system that generates political fragmentations and instability. Lebanese political elites exploited their positions in this system to forge clientelistic networks of services that often bypass institutional watchdogs and culminate in corrupt political practices. These elite practices hinder reform initiatives and financial security, manifesting in high public debt, poor infrastructure and a reliance on remittances and foreign aid. This situation was exacerbated by a massive influx of Syrian refugees into Lebanon as of 2011, which imposed a heavy burden on Lebanon’s economy and resources, while fueling tensions. Externally, both political and security threats obstructed the application of the dissociation policy. This is embodied in regional geopolitical variables, such as the interests and military activities of Israel, Iran and Saudi Arabia that can translate to increased political fragmentations in Lebanon, thus compromising opportunities for the formation of a solid, unified and autonomous Lebanese policy. On the international level, global economic conditions limit provisions of international funds. In addition, international donors and the role they play in international organizations can impinge on Lebanon’s sovereignty and independent decision-making processes. After surveying and analyzing a comprehensive set of political variables in the internal and external milieu of Lebanon, this thesis concludes that the implementation of an effective dissociation policy should factor in multiple contextual variables, else remain ineffective.